Chemical Kinetics Based Modelling Approaches and Tools for Investigating Complex Biological Systems: A Review - Anbumathi, P. (Asian Journal of Chemistry, 2014)
Biological systems are governed by their inherent complex molecular regulatory networks at multiple levels. It is the underlying chemical interactions that lead to the observed functions, phenotypic characteristics and diversity. However, it is not clear how such complex interactions at the molecular level impart specific functional characteristics of the cell/organism. This review presents a detailed account on how basic biochemical kinetics principles and computational tools are utilized to mathematically model and analyze such complex regulations. Such approaches are of crucial value in terms of (i) understanding disease mechanisms at molecular level, (ii) to predict possible drug targets (iii) to design new experiments and (iv) to combine the new experimental data along with known information to simulate drug specific pharmaco-kinetic behaviour of the system of investigation which might assist in treatment optimization. This review will also discuss a few case based examples reported in this emerging area to elucidate how such tools are successfully utilized to gain insights about biological systems for medical or drug discovery applications.